Prevalence and genotype/subtype distribution of hepatitis E virus (HEV) among wild boars in Japan: Identification of a genotype 5 HEV strain - Takahashi, Masaharu; Nishizawa, Tsutomu; Sato, Yukihiro; Miyazaki, Shinichi; Aikawa, Tatsuya; Ashida, Kozo; Tamaru, Tomoko; Oguro, Kunihiko; Hayakawa, Fumihiro; Matsuoka, Hiroyuki; Ozaki, Hideaki; Kodera, Yuuji; et al. (Virus research, 2020)
•Among 1880 wild boars captured in Japan during 2013–2019, 74 boars had HEV RNA.•Strains were classified into HEV-3 (3a/3b) (n = 50), HEV-4 (4i) (n = 23) and HEV-5 (n = 1).•wbJGF_19-1 shared 92.7 % identity with the prototype HEV-5 over the entire genome.•Genetically similar strains were identified in each area for over 10 years.•Wild boars continue to be important reservoirs for HEV in humans in Japan. To further investigate the prevalence of hepatitis E virus (HEV) infection and characterize HEV genomes among Japanese wild boars (Sus scrofa leucomystax), 1880 boars captured in 17 prefectures in Japan from 2013 to 2019 were studied. Overall, anti-HEV IgG was detected in 8.9 % and HEV RNA was detected in 3.9 % of boars, which was comparable with our previous studies during 2003–2013 (10.3 % and 3.5 %, respectively). Among 74 boar HEV strains obtained from infected boars in the present study, 50 (68 %) were classified into genotype 3 (3a and 3b), 23 (31 %) were classified into genotype 4 (4i), and the remaining strain (wbJGF_19-1) was classified into genotype 5. The wbGF_19-1 strain shared 92.7 % identity over the entire genome with the prototype genotype 5 strain (JBOAR135-Shiz09). The identification of the second genotype 5 HEV strain in a place that is located only 100 km from the site at which JBOAR135-Shiz09 was identified, suggests that genotype 5 HEV circulates within a relatively close range in Japan. Genetically similar HEV strains forming a clade were identified from wild boars living in each area during the observation period of 11–13 years, although the nucleotide sequence changed gradually, accounting for up to 3.4–3.6 % within the 412-nucleotide ORF2 sequence. Eight groups of boars with a cluster of HEV infections were observed, consisting of two, three or four infected offspring, presumably born to the same mother or offspring with their mother. These results suggest that wild boars continue to be important reservoirs for HEV infection in humans in Japan.